PROBLEMS OF INSTABILITY OF THE WORLD ECONOMY UNDER GLOBALIZATION - Dołęgowski, Tomasz; Hushko, Serhii; Kulishov, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
We examine the main trends of world economic development. The characteristic feature of the modern world is the acceleration of globalization development, caused by the achievements of scientific and technological progress. The increase in possibilities of global problem solving is accompanied by their exacerbation and degree of openness of public systems in conditions of modern globalization. We consider the interaction of international economic agents, the formation of interconnections, the inevitability of transition to a new and more progressive model of economic development – metaeconomy and the problems which are potentially able to cause negative consequences of the financial sector redistribution. There is a growth of social inequality in the world, resulting in increasing income disparities, which intensifies the migration process and thereby creates new problems as a result of the coexistence of people belonging to different civilizations, cultures and value systems.